Association of osteopenia with curve severity in adolescent idiopathic scoliosis: a study of 919 girls - Lee, Warren T. K.; Cheung, Catherine S. K.; Tse, Yee K.; Guo, Xia; Qin, Ling; Lam, T. P.; Ng, Bobby K. W.; Cheng, Jack Chun Yiu (Osteoporosis international, 2005)
Generalized osteopenia and spinal deformity occur concomitantly in adolescent idiopathic scoliosis (AIS) during the peripubertal period. No large-scale study has been performed to reveal the link between scoliotic deformity and bone-mineral status in AIS. In a cross-sectional study, the extent of scoliotic-curve severity in relation to bone-mineral status was examined for 619 AIS girls and compared with those of 300 healthy non-AIS counterparts aged 11-16 years. Curve severity was categorized into a moderate (10-39 degrees) and a severe group (> or = 40 degrees) based on Cobb angle. Anthropometric parameters, bone mineral-density (BMD) and bone mineral-content (BMC) of lumbar spine, proximal femur and distal tibia were determined by dual-energy X-ray absorptiometry and peripheral QCT. Differences in anthropometric parameters and bone mass among control and the AIS-moderate and AIS-severe groups were tested by one-way ANOVA. Association between Cobb angle and bone mass was determined by univariate and multivariate analyses. Mean Cobb angle of the moderate and severe groups were 25+/-6.3 degrees and 50.2+/-11.3 degrees, respectively. Arm span and leg length among the moderate and severe AIS subjects were almost all longer than for the controls from age 13 years. Age-adjusted arm span and leg length were significantly correlated with curve severity (p < 0.015). Starting from age 13 years, most axial and peripheral BMD and BMC of the moderate or severe AIS group was significantly lower than for the controls (p < 0.029). Age-adjusted Cobb angle was inversely correlated with BMD and BMC of the distal tibia and lumbar spine among AIS subjects (p < or = 0.042). The proportion of osteopenic AIS girls in the severe group was significantly higher than that in the moderate group (p < or = 0.033). Multivariate analysis indicated that Cobb angle was inversely and independently associated with axial and peripheral BMD and BMC (p < or = 0.042). To conclude, curve severity was an inverse and independent associated factor on bone mineral mass of AIS during peripuberty. The study implied that prevention of osteopenia could be as important as controlling spinal progression in the management of AIS.